From temporary bike lanes to a cycling oriented mobility paradigm. The case of Lyon during and after the pandemic of COVID-19 - Nathalie Ortar; Patricia Lejoux; Nicolas Ovtracht (Journal of Urban Mobility)
During the COVID-19 pandemic, cycling was presented as a potential solution to health and environmental challenges in everyday mobility. In Lyon (France), these street experiments posed two challenges for the city authorities: in the short term, to enable people to access essential services and shops while respecting the principles of physical separation; in the long term, to promote a new bicycle-oriented mobility paradigm that goes beyond infrastructure and includes velonomy and velomobility as a system. The aim of this article is to focus on the experience of tactical urbanism during the COVID-19 pandemic in the city of Lyon, the second largest city in France, and to investigate whether these pop-up infrastructures have facilitated a shift towards a cycling oriented mobility paradigm. In this article, we use three types of data: the first comes from a geomatic approach to map the changes, the second is an analysis of the policy context, and the third is the practices of cyclists. The results highlight that tactical urbanism accelerated the adoption of cycling through temporary infrastructure, structural changes, and expanded cycling routes. This approach improved connectivity, safety, and inclusivity while promoting cycling as a viable mode of transport. Despite initial political consensus, challenges emerged, including limited public recognition of these measures as policy and criticism of safety and navigation in certain designs. Efforts to institutionalize cycling policy have reduced car dominance and expanded public transport, but socio-spatial inequalities and low engagement from working-class communities persist. Inclusive cycling requires addressing diverse user needs, socio-economic barriers, and intersectional issues.